Efficacy and direct costs of chronic hepatitis C treatment with first generation NS3/4A protease inhibitors in a real life population - Piekarska, Anna; Koślińska-Berkan, Ewa; Wójcik, Kamila; Skubała, Anna; Jabłkowski, Maciej; Deroń, Zbigniew; Berkan-Kawińska, Aleksandra (Clinical and Experimental Hepatology, 2016)
Introduction: Recent years have brought a significant advance in chronic hepatitis C (CHC) treatment that includes development of direct acting antivirals (DAA). Two of them, boceprevir (BOC) and telaprevir (TVR), were first approved for treatment of patients infected with CHC genotype 1 in combination with pegylated interferon (P) and ribavirin (R). Our aim was to evaluate the efficacy and direct costs of BOC/PR and TVR/PR in a real life population. Material and methods : The study included adult patients qualified for the CHC Therapeutic Programme treated with TVR/PR or BOC/PR. Treatment was continued for 24 or 48 weeks. Sustained virological response, treatment discontinuation due to adverse events and lack of virological response rates were compared. Results : A total of 243 adult patients with CHC were included. TVR/PR and BOC/PR were administered in respectively 122 and 121 patients. Thirty-two patients (13%) were treatment-naïve, whereas liver cirrhosis/advanced fibrosis was observed in 138 patients (56.7%). Overall, 43.6% of patients achieved a sustained virologic response (SVR). In the BOC/PR group the SVR rate was significantly lower than in the TVR/PR group (33.1% vs. 54.1%; p = 0.00094). Lack of response to therapy was observed in 41.3% and 12.3% of patients receiving BOC and TVR, respectively (p < 0.00001). The direct cost of achieving SVR in one patient was 285 450 PLN with BOC and 185 757 PLN with TVR. Conclusions : The very low treatment efficacy may be the result of inclusion criteria that allowed treatment of patients with advanced liver fibrosis/liver cirrhosis or previous treatment failure. Telaprevir seems to be significantly more potent against hepatitis C virus, with similar safety and tolerance.